Effects of supplemental calcium salts of palm oil and chromium-propionate on insulin sensitivity and productive and reproductive traits of mid- to late-lactating Holstein × Gir dairy cows consuming excessive energy - Leiva, T. [UNESP]; Cooke, R. F.; Brandão, A. P.; Bertin, R. D. [UNESP]; Colombo, E. A. [UNESP]; Miranda, V. F.B. [UNESP]; Lourenço, L. A.C. [UNESP]; Rodrigues, S. M.B. [UNESP]; Vasconcelos, J. L.M. [UNESP] (American Dairy Science Association, 2018)
This experiment compared insulin sensitivity, milk production, and reproductive outcomes in dairy cows consuming excessive energy during mid to late lactation and receiving in a 2 × 2 factorial design (1) concentrate based on ground corn (CRN; n = 20) or including 8% (DM basis) of Ca salts of palm oil (CSPO; n = 20), and (2) supplemented (n = 20) or not (n = 20) with 2.5 g/d of Cr-propionate. During the experiment (d 0–203), 40 multiparous, nonpregnant, lactating 3/4 Holstein × 1/4 Gir cows (initial days in milk = 81 ± 2; mean ± SE) were offered corn silage for ad libitum consumption, and individually received concentrate formulated to allow diets to provide 160% of their daily net energy for lactation requirements. From d −15 to 203, milk production was recorded daily, blood samples collected weekly, and cow body weight (BW) and body condition score (BCS) recorded on d 0 and 203. For dry matter intake evaluation, cows from both treatments were randomly divided in 5 groups of 8 cows each, and allocated to 8 individual feeding stations for 3 d. Intake was evaluated 6 times/group. Glucose tolerance tests (GTT; 0.5 g of glucose/kg of BW) were performed on d −3, 100, and 200. Follicle aspiration for in vitro embryo production was performed via transvaginal ovum pick-up on d −1, 98, and 198. Mean DMI, net energy for lactation intake, as well as BW and BCS change were similar across treatments. On average, cows gained 40 kg of BW and 0.49 BCS during the experiment. Within weekly blood samples, CRN cows had lower serum concentrations of glucose, insulin, fatty acids, and insulin-to-glucose ratio compared with CSPO cows, suggesting increased insulin sensitivity in CRN cows. During the GTT, insulin-sensitivity traits were also greater in CRN versus CSPO cows. Supplemental Cr-propionate resulted in lower serum insulin concentrations and insulin-to-glucose ratio within CRN cows only, indicating that Cr-propionate improved basal insulin sensitivity in CRN but not in CSPO cows. During the GTT, however, Cr-propionate supplementation reduced hyperinsulinemia and insulin-to-glucose ratio across CSPO and CRN cows. Milk production, as well as number of viable oocytes collected and embryos produced within each aspiration, were not affected by treatments. Hence, replacing corn by Ca salts of palm oil in the concentrate did not improve insulin sensitivity in Holstein × Gir dairy cows consuming excessive energy during mid to late lactation, whereas Cr-supplementation was effective in improving basal insulin sensitivity in cows not receiving Ca salts of palm oil.
Keywords: chromium; dairy cows; energy intake; fat; insulin sensitivity